Narration in medical care. Selected aspects of narrative medicine in psychiatry - Patrycja Zurzycka; Katarzyna Wojtas (Termedia Publishing House, 2021)
Narrative in medical practice is a way to explore the nature of the disease in the face of the patient's uniqueness and individuality, regardless of the diagnosed disorder or disease. The narrative approach provides patients with a representation of their own story, a demonstration of interest on the part of their treatment team, and a positive relationship with the highest level of health care provision, always in relation to the patient's current health and life situation. The use of narrative medicine is important in forming relationships with patients or when professional work becomes a source of burnout and lack of perceived satisfaction. Aim of the study was to present selected issues related to the practice of narrative in medical care, including the care of patients with mental disorders. Thirty-three selected original papers were thoroughly analysed. All works were written in the period 2011-2020 and could be characterized as demonstrative or research papers and case studies. Medline, PubMed, SAGE, and other databases were used. Literature analysis confirms the presence of narrative medicine, including in the field of psychiatry. Researchers emphasize the importance of narrative in creating relationships with patients, shaping both their activity and involvement, as well as with members of the therapeutic team. In practice, narrative involves professionals expressing empathy, using narrative techniques, and being accountable when interacting with patients who discover themselves. The importance of narrative in the care of patients with various disorders, including mental disorders, is significant in providing care that is consistent with patients' expectations and needs.